Trimester- and Assay-Specific Thyroid Reference Intervals for Pregnant Women in China - Jinfang Xing; Enwu Yuan; Jing Li; Yuchao Zhang; Xiangying Meng; Xia Zhang; Shouhua Rong; Zhongxing Lv; Yuan Tian; Liting Jia (International Journal of Endocrinology)
Objective. The guidelines of the American Thyroid Association (ATA) recommend an upper limit reference interval (RI) of thyroid stimulating hormone (TSH) of 2.5 mIU/L in the first trimester of pregnancy and 3.0 mIU/L in subsequent trimesters, but some reported ranges in China are significantly higher. Our study aimed to establish trimester- and assay-specific RIs for thyroid hormones in normal pregnant Chinese women. Methods. In this cross-sectional study, 2540 women with normal pregnancies (first trimester, n=398; second trimester, n=797; third trimester, n=1345) and 237 healthy nonpregnant control subjects were recruited. Serum TSH, free thyroxin (FT4), thyroid peroxidase antibody (TPOAb), and thyroglobulin antibody (TgAb) levels were determined by automated chemiluminescence with an Immulite 2000 system (Siemens, Erlangen, Germany). After outliers were excluded, the 2.5–97.5th percentiles were used to define the RIs. Results. The RIs of thyroid function in the first, second, and third trimesters of pregnancy and in nonpregnant controls were 0.07–3.96, 0.27–4.53, 0.48–5.40, and 0.69–5.78 mIU/L for TSH and 9.16–18.12, 8.67–16.21, 7.80–13.90, and 8.24–16.61 pmol/L for FT4, respectively. Conclusion. The trimester- and assay-specific RIs of thyroid function during pregnancy differed between trimesters, which suggests that it is advisable to detect and avoid misclassification of thyroid dysfunction during pregnancy for women in Henan, China.